FINITE ELEMENT ANALYSIS OF AN RCC STAIR USING STAAD-PRO: A REVIEW - Gupta, Sumit; Pahwa, Sumit (International Journal of Research -GRANTHAALAYAH, 2018)
Our primary goal is to finish layout of stair is to ensure that the shape is safe and most economical in opposition to all feasible loading situations and to fulfill the feature for which they've built. Safety necessities should be in order that the structure is able to serve it cause with the hold fee. Detailed planning of the shape normally comes from several studies made by using city planners, investors, users, architects and different engineers. All the demanding situations faced via structural engineers had been taken as opportunities to develop software program’s together with STAAD-PRO, ETABS & SAFE, SAP etc., with ease of use. Software consisting of STAAD-pro is main commercial software program global for structural evaluation. The design outcomes the usage of STAAD PRO of a Stair case, for each regular and abnormal plan configuration, are used. Reinforced Concrete (RC) building frames are most common sorts of constructions in city India